TEST THE IMPACT OF UNCERTAINTY ON CAPITAL INVESTMENT FOR UK MANUFACTURING COMPANIES - WU, zheng (2008)
This thesis examines the impact of uncertainty on the levels of capital investment for manufacturing companies in UK. It is found from previous empirical studies that conclusions are varied, due to different theories, different forms of models, and employing different uncertainty measures. This study concentrates on the impact of energy (oil) price uncertainty and interest rates uncertainty on capital investment for UK manufacturing firms. Hence, an econometric model is constructed, including these two uncertainty proxy measures, together with Tobin's q, cash flow and lagged investment, to test the impact of uncertainty on capital investment.